High accuracy experimental determination of copper and zinc mass attenuation coefficients in the 100 eV to 30 keV photon energy range. (15th December 2015) - Ménesguen, Y; Gerlach, M; Pollakowski, B; Unterumsberger, R; Haschke, M; Beckhoff, B; Lépy, M-C
Abstract: The knowledge of atomic fundamental parameters such as mass attenuation coefficients with low uncertainties, is of decisive importance in elemental quantification using x-ray fluorescence analysis techniques. Several databases are accessible and frequently used within a large community of users. These compilations are most often in good agreement for photon energies in the hard x-ray ranges. However, they significantly differ for low photon energies and around the absorption edges of any element. In a joint cooperation of the metrology institutes of France and Germany, mass attenuation coefficients of copper and zinc were determined experimentally in the photon energy range from 100 eV to 30 keV by independent approaches using monochromatized synchrotron radiation at SOLEIL (France) and BESSY II (Germany), respectively. The application of high-accuracy experimental techniques resulted in mass attenuation coefficient datasets determined with low uncertainties that are directly compared to existing databases. The novel datasets are expected to enhance the reliability of mass attenuation coefficients.